Métodos de cenários prospectivos como ferramente de apoio ao planejamento relativo a substituição do atual uso do solo por florestamento: estudo de caso: a Bacia do Rio Ibicuí - RS - Cortez, Alexandre Schmidt (2007)
Planet Earth seen from outer space, as shown by numerous satellites photographs, reveals an impressive beauty. What is the cause of such beauty? Surely it is water. Throughout the centuries, the complexity of the multiple uses of water by man increased and produced an enormous set of degradation and pollution. On the other hand, the excessive multiple uses and permanent extractions for diverse means has decreased, considerably, the availability of water and has produced many problems of scarcity in many regions and countries. In 2004, after announcing an investment of 3 billion reals (approximately 1.6 billion dollars) in forestry and the opening of a cellulose industry for the manufacturing of paper in the southern half of the state of Rio Grande do Sul, Votorantim Celulose e Papel, began to be criticized. The main criticisms claim that eucalyptus is an exotic specie which increases water deficit, reduces soil fertility and pH, frightens the fauna, the plantations form great landed estates and monoculture, presents little contribution for the generation of jobs, provokes rural exodus, diminishing property value and which could cause a serious environmental damage in Rio Grande do Sul. This paper shows subsidies for discussion and elaboration of prospective scenarios, about matters related to hydric, social, economic, environmental, technological, political and legal resources, previewing a temporal horizon of the year of 2020, for the Ibicuí River Hydrographic Basin. Key points were identified through future bearer events and the perception of the principal factors which influence the current system. The general objective of research is to evaluate the perception of the involved factors on the effects caused by the substitution of the use of the soil for eucalyptus in relation to hydric resources, motivating a stage setting as a tool for the management strategy and basing committee decision planning, with the intuition to avoid future surprise and unpredictability. It was used the "Grumbach method" and the "Lince method" obtaining as result three sceneries More Probable Scenery, Ideal Scenery, Scenery of Tendency.